Antipsychotics use in the community of Thessaloniki, Greece - Papaioannidou, Paraskevi; Kasviki, Paschalina (Vojnosanitetski pregled, 2020)
Background/Aim. Under the current financial crisis in Greece, an effort has been made by the Greek health authorities to encourage generic prescribing, in order to lower medicinal cost. The purpose of this work was to study antipsychotics use, and to calculate utilization of generics in antipsychotics sales in a sample from the medicines market of Thessaloniki, the second largest city in Greece. Methods. A sample of antipsychotics registered sales was collected using the new Electronic Health Records that have been applied in pharmacies during the last years in Greece. The sample corresponded to a small amount of sales from the market of Thessaloniki during the period July 2014–June 2015, including only community and no hospital sales. All brand names (prototype and generics) of antipsychotics and their relative ratios in the sales were estimated, and the percentage of generics in the sale of each medicine was calculated. The amount of medicines was estimated in Defined Daily Doses (DDDs) of the reference/prototype drug and its generics. Results. Olanzapine, quetiapine, haloperidol and risperidone sales corresponded to 77% of total antipsychotics sales with percentages of sales 25%, 19%, 19% and 14% respectively. The percentage of sales of other antipsychotics was 7% for amisulpride, 6% for aripiprazole, 4% for ziprasidone and 3% for clozapine. Generic use corresponded to 41% of total sales of antipsychotic drugs (10.884 DDDs out of 26.433 DDDs). Concerning second generation antipsychotics, generic use was high for amisulpride, olanzapine, risperidone and quetiapine. Conclusion. In the study sample, second generation antipsychotics corresponded to 78% of sales in the community of Thessaloniki. Haloperidol utilization was also notable. Considering Greek practices, the percentage of generics in antipsychotics sales was very high even for some of the newest antipsychotics.
Keywords: antipsychotic agents; drugs, generic; prescription drugs; economics, pharmaceutical; greece.